Preparation of maltotriitol-rich malto-oligosaccharide alcohol from starch. (January 2017) - Niu, Dandan; Li, Pujun; Huang, Yongsheng; Tian, Kangming; Liu, Xiaoguang; Singh, Suren; Lu, Fuping
Graphical abstract: MOS: Malto-oligosaccharides, a mixed sugar mainly composed of maltose, maltotriose, glucose, and other malto-oligosaccharides with a DP of 4–8. MOSA: Malto-oligosaccharide alcohols, a mixture of oligosaccharide alcohols mainly composed of maltitol, maltotriitol, sorbitol, and other malto-oligosacharides alcohols with a DP of 4–8. Highlights: Maltotriitol-rich MOSA is much more recognized sugar alcohols widely used as sweetener. A novel process was developed and optimized for preparing maltotriitol-rich MOSA from starch. Cooperative actions of B. naganoensis pullulanase, B. amyloliquefaciens α-amylase, and barley bran β-amylase on liquefied starch yielded maltotriose-rich MOS. Abstract: Malto-oligosaccharide alcohols (MOSA) are one of the most important sugar alcohols widely used as sweetener in food, cosmetic, and pharmaceutical industries in recent years, of which maltotriitol-rich MOSA is much more recognized. With the aim of preparing maltotriitol-rich MOSA from starch, a novel process was developed and optimized. Starch was first liquefied with thermostable Bacillus licheniformis α-amylase. The liquefied starch was then saccharified to yield maltotriose-rich malto-oligosaccharides under the cooperative actions of Bacillus naganoensis pullulanase, Bacillus amyloliquefaciens α-amylase, and barley bran β-amylase. The maltotriitol-rich MOSA was finally prepared by chemical hydrogenation. Under the optimized conditions, maltotriitol-rich MOSA containing 42.18% maltotriitol was obtained with a conversion rate of 104.57% from starch. The process can be employed for large-scale preparation of maltotriitol-rich MOSA, and a further modification of the process can lead to the formulation of various types of MOSA with different percentages of components of sugar alcohols.